Terapi Virtual Reality (VR) terhadap Skala Nyeri Penderita Osteoarthritis (OA) Post Total Knee Replacement (TKR) - Jun Absa B; Masfuri Masfuri; Liya Arista (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to analyze the effectiveness of Virtual Reality (VR) technology on pain scales in post-TKR osteoarthritis patients. Using previously defined keywords, this research uses the literature review method, which originates from the database, namely ClinicKey Nursing, EBSCOhost, ProQuest, and Embase with Publish in 2018-2022. The results showed that after the four databases were determined, 511 articles were produced, of which Clinickey Nursing (n = 41), EBSCOhost (n = 17), EMBASE (n = 3), and ProQuest (n = 450). First and second screening (n = 81) (=26). duplication and filtering of titles/abstracts, and based on inclusion and exclusion criteria, the number of articles were grouped into 5 (n=5). In conclusion, VR technology devices still need to do an in-depth study regarding the effectiveness of their use as a distraction technology in post-TKR patients. Specific assessment of the use of VR technology in terms of Visualization, Auditory, and Type of VR Devices used to control functions. Keywords: Osteoarthritis, Pain Scale, Total Knee Replacement, Virtual Reality